2020
DOI: 10.1097/md.0000000000020332
|View full text |Cite
|
Sign up to set email alerts
|

Foam sclerotherapy compared with liquid sclerotherapy for the treatment of lower extremity varicose veins

Abstract: Background: There is a continued discussion on which is the best sclerosant to treat lower extremity varicose veins. Therefore, we did this meta-analysis to determine that foam sclerotherapy versus liquid sclerotherapy, which could perform better in the treatment of lower extremity varicose veins. Materials and methods: We independently searched 5 databases from inception to February 1, 2019, for randomized controlled trials and prospective controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…In recent years, several clinical trials have demonstrated decreased efficacy of liquid sclerotherapy when compared to foam for treatment of saphenous vein varicosities. A meta-analysis and a systematic review both demonstrated increased efficacy when evaluating ultrasound-demonstrated elimination of reflux [ 220 , 221 ].…”
Section: Advances In Minimally Invasive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several clinical trials have demonstrated decreased efficacy of liquid sclerotherapy when compared to foam for treatment of saphenous vein varicosities. A meta-analysis and a systematic review both demonstrated increased efficacy when evaluating ultrasound-demonstrated elimination of reflux [ 220 , 221 ].…”
Section: Advances In Minimally Invasive Treatmentmentioning
confidence: 99%
“…However, another trial measuring outcomes at 3 months determined that although mean changes in CIVIQ scores were comparable between groups, patient and physician satisfaction with foam sclerotherapy was significantly higher [ 225 ]. Liquid therapy was noted to have overall similar or perhaps fewer complications, although both therapies were determined to be generally safe [ 221 , 226 228 ]. Adverse events in liquid sclerotherapy were similar to those of foam sclerotherapy.…”
Section: Advances In Minimally Invasive Treatmentmentioning
confidence: 99%
“…Because sclerotherapy is divided into 2 major kinds -liquid and foam -there are different risks of side effects [3,18,[19][20][21][22]. Foam sclerotherapy has a relatively high percentage of complications, but it can achieve higher stability of clinical effectiveness in treating varicose veins of lower limbs than liquid sclerotherapy [3,11,19,20]. Several sclerotherapy adverse effects have been reported, and the procedure complications can be divided into common, uncommon, or rare (Table 1, 2).…”
Section: A E S T H E T I C C L I N I C S M E D I C a L D I N I C S A E S T H E T I C A N D M E D I C I N E C L I N I C S D O C T O R ' S mentioning
confidence: 99%
“…El daño endotelial ocurre de forma rápida, a los pocos minutos de su administración, y puede extenderse hacia las capas media y adventicia en virtud de la concentración del esclerosante empleado que, a su vez, es determinante en la aparición de HPE [1, 5,10]. Es recomendable ajustar la concentración al diámetro del vaso a tratar, aunque no hay diferencias significativas en cuanto a HPE entre la utilización de esclerosante líquido o en forma de MPOL [11,12]. La glicerina cromada es el representante de los denominados esclerosantes irritantes.…”
Section: Introductionunclassified